Analysis of the Concept of Bill Discounting in Sharia Banking (DSN-MUI Fatwa Study No. 58/DSN-MUI/V/2007) - Sahlan Sahlan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2021)
This research examines the analysis of the DSN-MUI fatwa No. 58 / DSN-MUI / V/ 2007 concerning Hiwālah practice which is currently being applied in Islamic Financial Institutions. Bill discounting is a contract for providing services to a Sharia (Islamic) Bank in the form of takeover of customer debt by the Bank. Bill discounting is not intended to seek profit, but to facilitate the implementation of financing because Bill Discounting includes multi-service financing. The main objective of DSN-MUI in implementing the contract is to maintain the common good. Thus allowing for quick and simultaneous debt settlement. In this article, the main problem is how the concept of bill discounting in Islamic Banking according to the DSN fatwa No. 58 / DSN-MUI / V / 2007. The research method used is library research with the uṣūlī approach. The conclusion of this study is that one of the principles of DSN is hifż al-māl (safeguarding assets) with financial institutions obliged to safeguard (amānah) customers' funds as well as possible.